Potential Use of Mosambi Peel-Based Bioenzymes for the Wound Management in Animals - Phutela, Urmila Gupta; Arora, Richa; Kumar, Ajeet; Aggarwal, Yashika (The Indian Journal of Animal Reproduction, 2025)
Wound healing is one of the major issues faced by animal rearers. The common afflictions are horn and foot injuries in animals. The therapeutic treatment involves the usage of costly antibiotics, which not only causes resistance to antibi otics but also alters the gut microflora. The present study was carried out with the objective to produce mosambi-peel based bioenzymes having antioxidant properties and further exploited for animal wound healing. The bioenzymes were characterized with respect to physico-chemical, enzymatic, color and microbiological profile. The presence of various antioxidant compounds including pterostilbene, hesperetin, aloin A, ononin, quercetin 3,7-dirhamnoside, isoorientin 2’-O-rhamnoside, saponarin was confirmed by LC-MS. Further, the bioenzyme solution sprayed on animal wounds stopped bleeding within 2-3 minutes and showed normal healing indicated by granulation tissue without pus pocket formation or any other side effects even in absence of any antibiotic treatment. In addition to this, it also acted as fly repellent for 5-6 h. Thus, the mosambi-peel based bioenzymes could serve as a cost-effective alternative to swap anti biotic therapy for wound healing in animals. Furthermore, the issue of solid waste management will be addressed by valorization of horticultural waste to bioenzymes.